ANTIMICROBIAL EFFECT OF DODONAEA VISCOSA JACQ.EXTRACTS AGAINST SOME PATHOGENIC MICROORGANISMS - Esmaeel, Zubaida; AL-Jobori, Kamil (Iraqi Journal of Science, 2024)
The present study has been conducted to evaluate the inhibitory effects of theaerial plant part (leaves and bark) extracts of D. viscosa before and during floweringagainst some pathogenic bacteria for human, plants, and against yeast (Candidaalbicans) by using different polarity organic solvents: Ethanol and Diethyl ether.The agar well diffusion method was used to evaluate the inhibitory actions of theseextracts with eight concentrations: 0, 2.5, 5, 10, 20, 30, 40 or 50 mg/ml. TheMinimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration(MBC) values were also determined, in addition to compare the results of the plantextracts with the results of the susceptibility of pathogenic microorganisms forantibiotics, The completely randomized design (CRD) was used with threereplications. Better effect was observed in the liquid dilution assay with all extractsshowing a degree of effect. The results showed that ethanolic extracts of the barkand leaves, and diethyl ether extracts of the leaves demonstrated clear inhibitoryeffect against the tested microorganisms. ethanolic extracts of the bark was superiorover leaf extracts in the inhibitory effects on the growth of C. albicans. In general,the results showed no significant differences between the concentrations of 30, 40 or50 mg/ml. The microbial screening showed that the MIC of ethanolic extracts of thebark before and during flowering was at a concentration of 2.5 mg/ml, and for leafextracts ranged between 2.5-10 mg/ml. As for MBC effects was ranged between 5-50 mg/ml, depending on the type of solvents, microorganism and the period ofcollection (before or during flowering). In comparison with antibiotics, the resultsshowed high similitude between D. viscosa extracts at concentrations of 30, 40 or 50mg/ml and antibiotics against the tested microorganisms. When our results compareswith other studies that conducted in other parts of the world, we concluded that thetype of solvent, method of extraction, period of collection (before or duringflowering) and the geographical distribution of D. viscosa significantly affect therate of the chemical components and its effect against microorganisms.